Process development for bio-ethanol production using wheat straw biomass - Ruíz, Héctor A. (2010)
Wheat straw is nowadays being considered a potential lignocellulosic raw material (LCM) for fuel-ethanol production as an alternative to starch or sugar-containing feedstock. In this work, the evaluation of process variables (temperature, residence time and particle size) autohydrolysis pretreatment of wheat straw for ethanol production was addressed by means of design of experiments. The recovery of hemicellulose derived sugars (HDS) in the liquid fraction and the ethanol production of the solid residue obtained after filtration of pretreated material were considered as response variables to different processes conditions. Results show that the optimal conditions were 200 ºC and 30 min, leading to HDS recovery yield of 31.88% of HDS content in raw material and ethanol production yield of 80.1% of theoretical.